Annular Rupture Leading to Fatal Complications in an Elderly Patient with Calcified Aortic and Mitral Annulus Undergoing Transapical Aortic Valve Implantation - Haldenwang, Peter L.; Bechtel, Matthias; Schlömicher, Markus; Lindstaedt, Michael; Strauch, Justus T. (The Thoracic and Cardiovascular Surgeon, 2013)
This case illustrates the awareness that must be taken of the high morphological risk due to the calcifications of both, the aortic and mitral annulus in elderly patients when performing transapical aortic valve implantation. In an 86-year-old, multimorbid woman (logistic EuroSCORE = 27%) with symptomatic aortic stenosis (annular diameter = 23.4 mm) and severe mitral annular calcification, the implantation of a 26-mm Edwards SAPIEN (Edwards Lifesciences, Irvine, California, United States) valve in aortic position was primary successful, with no paravalvular leakage, valve instability, or coronary malperfusion. Second, a persisting transmural bleeding led to hypovolemic shock, which could not be stabilized even after going on cardiopulmonary bypass, and the patient died in the operation room. The autopsy showed a subvalvular ventricular rupture due to a transmural perforation of the calcified fibrotic annulus during valvuloplasty.
Keywords: aortic valve and root; heart valve; transapical; surgery; complications; outcomes; elderly